High rate of chromosome abnormalities detected by fluorescence in situ hybridization using BCR and ABL probes in adult acute lymphoblastic leukemia - Rieder, Harald; Bonwetsch, Christine; Janssen, L. A. J.; Maurer, J.; Janssen, Johannes W. G.; Schwartz, Stefan; Ludwig, Wolf-Dieter; Gassmann, Winfried; Bartram, Claus R.; Thiel, Eckhard; Löffler, Helmut; Gökbuget, Nicola; et al. (Leukemia, 1998)
The value of dual-color fluorescence in situ hybridization (FISH) with BCR and ABL probes for the detection of the Philadelphia (Ph) translocation and of other alterations involving ABL and/or BCR was evaluated in adult acute lymphoblastic leukemia (ALL). One hundred and four patients were studied prospectively using interphase nuclei FISH, chromosome analysis (CA), and PCR assays for the chimeric BRC/ABL transcript. FISH detected a Ph translocation in 24 cases (23.1%), as was confirmed by CA and/or PCR. FISH revealed a false positive diagnosis of a Ph translocation in four cases (5% false positive rate). Among 54 cases with combined FISH, CA and PCR assays, FISH failed to establish a correct diagnosis in 3.7%, PCR in 5.6%, and CA in 7.4%. The combination of two screening methods led to discrepant results in 9.3% (FISH + PCR), 11.1% (FISH + CA), or 13% (CA + PCR) of the cases. In seven of 80 (8.8%) Ph-negative patients, gain of BCR and/or ABL was identified. Overall, FISH detected alterations of the BCR and/or ABL genes with an incidence of 29.8% of the current study. Due to the possibility of false positive diagnosis of a Ph translocation using dual-color FISH the combination with chromosome and/or RT-PCR analyses is recommended in adult ALL patients.
Gesehen am 08.01.2024